Evaluation of disintegrant properties of breadfruit (Artocarpus altilis) starch in metronidazole tablets formulations - Nkemakolam Nwachukwu; Chibueze Austin Odoemena; Sunday Okorie Abali (African Journal of Pharmaceutical Research and Development (AJOPRED), 2024)
Disintegrants are significantly important for tablet break up and release of the active drug for dissolution in conventional drug delivery. This study aimed at evaluating the disintegrant properties of Artocarpus altilisi (bread fruit) starch in metronidazole tablet formulations. The matured peeled fruits were soaked in 0.2 %w/v sodium metabisulphate, grated, and the slurry washed with distilled water through a muslin cloth. The bread fruit starch (BFS) obtained was dried at 60 °C, milled and sized (125 µm). The BFS was characterized using standard methods and applied as disintegrant in the formulation of metronidazole tablets respectively at 6, 12 and 18% using wet granulation method. Corn starch BP was used as comparing standard. The metronidazole granules were evaluated for their micromeritic properties and thereafter compressed into metronidazole tablets. Evaluation of the metronidazole tablets for their physical properties, assay and dissolution studies were done using British Pharmacopoeia methods. The metronidazole granules were flowable and compressible. Metronidazole tablets had good physical properties: minimal weight variation (0.526  ± 0.13 - 0.531 ± 0.10 g), hardness (5.00 ± 0.12 – 6.42 ± 0.10kg), disintegration time < 15 min and friability < 1 %. Dissolution of metronidazole from the tablets containing BFS complied with British Pharmacopoeia criteria. Breadfruit starch compared well with corn starch BP as disintegrant in metronidazole tablet formulation.